Capillariosis Infection of the liver in Rainbow Trout - ΠΝΕΥΜΑΤΙΚΑΤΟΣ Γ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The author described, for the first time in Greece, a case of liver Capillariosis (C. Petruschewskii) in rainbow trout, observed in a unit of trout culture. The author studied and described the clinical, anatomopathological and histological changes of the disease and concluded that hepatic Capillariosis in rainbow trout runs asymptotnatically without producing untorward consequences in the unit.